Jednoprzestrzenne kościoły romańskie z terenu Wielkopolski - Różański, Artur (Folia Praehistorica Posnaniensia, 2018)
‘Rural’ ecclesiae laicorum have remained mute witnesses of our history; they have been deserted, forgotten and frequently falling into ruin. Single-nave Romanesque churches from the territories of Poland have not been much interest for the scholars of the Middle Ages. A full monograph on such churches from Greater Poland has not been written yet. This remains in a striking opposition to analogues buildings from Western Pomerania, Silesia or the New March. The only incomplete and to a large extent outdated work on this subject is Stanisław Wiliński’s paper Granite village churches of 12th century in Greater Poland or an exiguous paper by Alicja Karłowska- Kamzowa addressing the question of their foundation. The main aim of my book is the presentation of single-nave churches from Greater Poland erected in the period between the second half of the eleventh century and the end of the thirteenth century, in their historical and settlement context. Only churches that have been subject to archeological excavations have been included. Therefore, two factors determined whether a church has been chosen and included in this study: firstly, some archeological excavations must have been carried out within it, and secondly, the church must have played a basic role as a Christianization centre for ‘rural’ areas.